The assessment of trunk recovery in stroke patients using 3D kinematic measures. (April 2020) - Carozzo, Simone; Serra, Sebastiano; Pignolo, Loris; Tonin, Paolo; Cerasa, Antonio
Highlights: We propose a 3D kinematic system for evaluation of trunk recovery in stroke. Significant correlation between kinematic measures and clinical outcome is found. Measurement of lateral pelvic explains trunk control test variability. Kinematic parameters of trunk can be used as integrated assessment. Abstract: The kinematic analysis of trunk recovery in patients with stroke has sparsely been investigated. This study is aimed at evaluating the validity of a kinematic system for measuring trunk movements. Forty-five right-handed stroke patients in the post-acute phase were assessed in a within-subject design, before and after intensive conventional neurorehabilitation treatment. An eight-camera system was used to analyze the three-dimensional (3D) kinematics of trunk during typical displacements (anterior/posterior and right/left lateral). Kinematic trunk measurements and clinical evaluations were performed immediately in a blind fashion before and after rehabilitation treatments. Of the 9 kinematic variables, 4 showed a significant relationship with the clinical measure of the trunk: Trunk Control Test (TCT). Among these, only the kinematic evaluation of the lateral pelvic was the best predictor ( R 2 = 0.2; p -level< 0.006; beta= 0.41) of clinical recovery measured with TCT. Here, we present a 3D kinematic system for assessing trunk impairments in stroke patients. We found that different kinematic variables reflect motor recovery as assessed by conventional clinical scale. Further evaluations, including reliability analysis and application on patients with gait impairments, are required.